PENINGKATAN PENDAPATAN MASYARAKAT URBAN - Hermanto, Bambang; Hamizar, Hamizar; Kurniasari, Isnaini Hijriyah; Setiawati, Sri (JURNAL LENTERA BISNIS, 2019)
Depok City growth as a develop City in Indonesia and as the result Depok became one of the cities that overrun by the urban from various of region in Republic of Indonesia. This research is aimed to know how far the role of urban in the minority area around Bus station in especially Depok City and people of Pancoranmas district in general in empowering the people’s economy especially in supporting, guiding, and developing retail business. The method used to analyzethis research is linear regression, correlation coefficient and determination coefficient. The result shown that the earnings and business run by the urban in Depok is good. However, there is a legality problem regarded the government license which is caused by the majority of the urban do not have a clear identity data and as the result the business of the urban won’t last longer. Therefore, Depok Local Government must take role especially the Department of Population and Civil Registration, Social Affairs and Department of Cooperatives of Small, Medium Enterprise in giving accompaniment towards the urban entrepreneursKeywords: Urban, Retail Business, Earnings.Depok City growth as a develop City in Indonesia and as the result Depok became one          of the cities that overrun by the urban from various of region in Republic of Indonesia. This research is aimed to know how far the role of urban in the minority area around Bus station in especially Depok City and people of Pancoranmas district in general                   in empowering the people’s economy especially in supporting, guiding, and developing retail business. The method used to analyzethis research is linear regression, correlation coefficient and determination coefficient. The result shown that the earnings and business run by the urban in Depok is good. However, there is a legality problem regarded the government license which is caused by the majority of the urban do not have a clear identity data and as the result the business of the urban won’t last longer.                    Therefore, Depok Local Government must take role especially the Department                         of Population and Civil Registration, Social Affairs and Department of Cooperatives of Small, Medium Enterprise in giving accompaniment towards the urban entrepreneurs Keywords: Urban, Retail Business, Earnings.